Solving linear and non-linear stiff system of ordinary differential equations by multi stage homotopy perturbation method - Chowdhury, Md. Sazzad Hossien; Hashim, I.; Hosen, Md. Alal (IRAJ Research Forum, 2016)
In this paper, linear and non-linear stiff systems of ordinary differential equations are solved by the multi-stage homotopy perturbation method (MHPM). The MHPM is a technique adapted from the standard homotopy perturbation method (HPM) where standard HPM is converted into a hybrid numeric-analytic method called multistage homotopy perturbation method (HPM). The MHPM is tested for several examples. Comparisons with an explicit Runge-Kutta-type method (RK) demonstrate the promising capability of the MHPM for solving linear and non-linear stiff systems of ordinary differential equations.